2013
DOI: 10.1037/a0034090
|View full text |Cite
|
Sign up to set email alerts
|

Positive and negative workplace relationships, social satisfaction, and organizational attachment.

Abstract: We examine how employees' centrality in the networks of positively valenced ties (e.g., friendship, advice) and negatively valenced ties (e.g., avoidance) at work interact to affect these employees' organizational attachment. Using 2 different samples (154 employees in a division of a food and animal science organization and 144 employees in a product development firm), we found that employees' centrality in positive and negative tie networks at work were related to their organizational attachment indirectly v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
121
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 132 publications
(143 citation statements)
references
References 83 publications
(103 reference statements)
7
121
0
Order By: Relevance
“…This is in accordance with what Venkataramani, Labianca, and Grosser [29] described, as "job satisfaction has been defined as a psychological state represented by cognitive and affective indicators resulting from the evaluation of one's job experiences" (p. 1031).…”
Section: Utilization Of Competencesupporting
confidence: 60%
See 3 more Smart Citations
“…This is in accordance with what Venkataramani, Labianca, and Grosser [29] described, as "job satisfaction has been defined as a psychological state represented by cognitive and affective indicators resulting from the evaluation of one's job experiences" (p. 1031).…”
Section: Utilization Of Competencesupporting
confidence: 60%
“…Venkataramani, Labianca, and Grosser [29] In some hospitals, the consultant is treated in a solely functional and impersonal way. Hence, the competence of the doctor is interpreted at a strictly professional or educational level, while the person behind the competence is of little importance [37].…”
Section: The Client Companies' Involvementmentioning
confidence: 99%
See 2 more Smart Citations
“…In support of the validity of the three-item Seashore Turnover Intentions Scale, Meriac, Slifka, and LaBat (2015) found that turnover intentions strongly negatively correlated with job satisfaction (r = -.67). Additionally, Venkataramani, Labianca, and Grosser (2013) Organizational commitment. Affective organizational commitment was measured using a shortened version of the Affective Commitment Scale (ACS; Allen & Meyer, 1990;).…”
Section: Discussionmentioning
confidence: 99%